Peranan Pembiayaan Murabahah dalam Meningkatkan Pendapatan Usaha - Eka Putra Nuzuri; Andriani (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Murabahah financing is the most popular in the BMT Lantasir Pesantren Kediri. It is using aqad wakalah that give solving or helping to customer whose want to have goods. Aqad wakalah means that authorization spilled by one party to another party on the representative aspects. Beside of customers has money financing propose, also could to propose goods financing. The most customers of murabahah financing in BMT Lantasir are retailers. So, they can choose murabahah financing to get modals or adding goods stock in their business for increasing and reaching return.The research is use to qualitative approach with cases study that gets data by fact related to theme research, and will be depth analization. The respondens are manajer, common (pembantu umum), customer service, account officer and customers. For collecting data’s process are interview, observation and documentation. While analysis’s process are data reduction, data explanation and making conclusion.The result showing that murabahah financing has a role to change customer’s income. The role of murabahah financing seems on the increasing customer’s income table. It shows that customer’s income are increase by 30%, 50% and 70%. Moreover, there is a customer who has settled job and has corn farm is get return on harvest season. Based on analysis is murabahah financing has the most important role to fulfill customers needed such as money and goods, also to increase income customers changing.